Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1007/s12035-013-8396-8
|View full text |Cite
|
Sign up to set email alerts
|

Astrocyte-Derived Sonic Hedgehog Contributes to Angiogenesis in Brain Microvascular Endothelial Cells via RhoA/ROCK Pathway After Oxygen–Glucose Deprivation

Abstract: The human adult brain possesses intriguing plasticity, including neurogenesis and angiogenesis, which may be mediated by the activated sonic hedgehog (Shh). By employing a coculture system, brain microvascular endothelial cells (BMECs) cocultured with astrocytes, which were incubated under oxygen-glucose deprivation (OGD) condition, we tested the hypothesis that Shh secreted by OGD-activated astrocytes promotes cerebral angiogenesis following ischemia. The results of this study demonstrated that Shh was mainly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 43 publications
0
56
2
Order By: Relevance
“…Down-regulation of Shh expression in astrocytes disrupts the BBB (Alvarez et al , 2011), suggesting that stimulation of astrocytic Shh production could promote restoration of BBB integrity. Shh further induces upregulation of angiopoietin-1 in astrocytes, which is necessary for vessel maturation (He et al , 2013). …”
Section: Astrocytes In Neurorestorationmentioning
confidence: 99%
“…Down-regulation of Shh expression in astrocytes disrupts the BBB (Alvarez et al , 2011), suggesting that stimulation of astrocytic Shh production could promote restoration of BBB integrity. Shh further induces upregulation of angiopoietin-1 in astrocytes, which is necessary for vessel maturation (He et al , 2013). …”
Section: Astrocytes In Neurorestorationmentioning
confidence: 99%
“…Altogether these data suggest a dual signaling of Hh proteins; whereas Hh proteins prime the initial steps of angiogenesis, mostly cytoskeletal activation, cell elongation, and extended survival by acting through noncanonical signals, the indirect effects of Hh on Gli-dependent secretion of VEGF and Ang1 and 2 by mesenchymal cells may provide the additional contribution required to enhance endothelial cell proliferation, migration, survival, and vessel maturation [127]. Similar mechanism implicating RhoA-/Rho-associated protein kinase (ROCK) pathway has been described in a co-culture model of brain microvascular endothelial cells and astrocytes during oxygen-glucose deprivation [128]. In fact, after oxygen-glucose deprivation, astrocytes released Shh which directly promoted angiogenesis via the RhoA/ROCK pathway.…”
Section: Implicated Mechanisms In the Direct Effects Of Hh On New Vesmentioning
confidence: 76%
“…Middle cerebral artery occlusion is associated with increased mRNA encoding both Shh and its transcription factor Gli1, already a few hours after induction of brain ischemia [38]. By employing a co-culture system of brain microvascular endothelial cells (BMECs) and astrocytes, incubated under oxygen-glucose deprivation (OGD) condition, it has been demonstrated that Shh is secreted by activated astrocytes and promotes proliferation, migration, and tube formation of BMECs [39]. In this assay, proliferation, migration, and tube formation of BMECs may be suppressed by silencing the Ras homolog gene family member A (RhoA) and blocking Rho-dependent kinase (ROCK) [39].…”
Section: Hedgehog In the Ischemic Brainmentioning
confidence: 99%
“…By employing a co-culture system of brain microvascular endothelial cells (BMECs) and astrocytes, incubated under oxygen-glucose deprivation (OGD) condition, it has been demonstrated that Shh is secreted by activated astrocytes and promotes proliferation, migration, and tube formation of BMECs [39]. In this assay, proliferation, migration, and tube formation of BMECs may be suppressed by silencing the Ras homolog gene family member A (RhoA) and blocking Rho-dependent kinase (ROCK) [39]. Not only ODG, but also oxidative stress has been shown to have the ability of activating the Shh pathway in cultured cortical neurons [40].…”
Section: Hedgehog In the Ischemic Brainmentioning
confidence: 99%